Psychiatric hospitalizations due to alcohol and drug consumption among young people in Ceará, Brazil - Balbinot, Alexandre Dido (Clinical and Biomedical Research, 2017)
Introduction: This study aimed to analyze the evolution of psychiatric hospitalizations among children and adolescents due to psychoactive substance use in the public health system in the state of Ceará, Brazil. Hospitalizations between 2000 and 2015 were used as indicators. Methods: Ecological study using secondary data. Data analysis was performed with the software Stata 11.1® from StataCorp LLC (Texas/USA) using Poisson regression with robust variance and Spearman correlation. A 95% confidence interval was adopted and significance level was set at 5%. Results: The variables hospitalization rates and mean length of hospital stay did not vary significantly. There was no variation when data were stratified by sex. A negative correlation was found between hospitalization rates and mean length of hospital stay (P < 0.05) among girls, but not among boys or overall population. Conclusion: In Ceará, the creation of alternative mechanisms to hospital admission has not resulted in reduced hospitalization rates. Keywords: Hospitalization, Ceará (Brazil), mental health, public health system.